Profiling the New Zealand Police Trainee Physical Competency Test - Dawes, J. Jay; Scott, Jordan; Canetti, Elisa F. D.; Lockie, Robert G.; Schram, Ben; Orr, Robin M. (Frontiers in Public Health, 2022)
Police officers require a certain amount of occupational fitness to successfully perform physically demanding tasks. As such, trainees are required to undergo training to develop their ability to perform such tasks. The physical competency test (PCT) is a 400 m obstacle course consisting of key police occupational physical tasks used to evaluate a trainee’s ability to complete tasks that a police officer is expected to perform whilst on duty. The purpose of this study was to profile the PCT in a police recruit population. Retrospective data for 813 male (age = 27.41 ± 5.92 years, body mass = 83.98 ± 14.03 kg, height = 179.23 ± 10.50 cm, BMI = 25.85 ± 3.92 kg/m2) and 372 female (mean age = 27.01 ± 6.45 years, mean weight = 67.14 ± 8.60 kg, mean height = 168.14 ± 6.46 cm and mean BMI = 23.61 ± 2.52 kg/m2) police trainees from the New Zealand Police Constabulary Recruitment database were provided for analysis. Anthropometric data, including height, body mass, and BMI were provided, in addition to trainee PCT time. Data were split by sex and age. Significant differences were observed between sexes for all anthropometric measures and PCT time (p<0.001). Generally, in both the male and female groups, younger recruits tended to perform better than the older recruits with results between the ‘under 20’ and the 20-24-year-old-age groups performing significantly better than the 35–39-year-old-age group in both sexes, and the 25-29-year-old-age group performing significantly better than the 35-39-year-old-age group in female officers. The data provided in this study provides a profile for performance of male and female recruits of various ages on the PCT in preparation for entry, or re-entry following injury, into the NZ Police. However, given that the PCT is considered a measure of occupational task performance, consideration should be given to the use of sex and age neutral requirements as the occupational tasks performed by police officers exhibit the same traits regardless of sex or age.